CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

(6abb2+12ac2bc) divided by (6ab) gives .


Correct Answer
A
(b+2c)
Your Answer
B
(b2c)
Your Answer
C
(2bc)

Solution

The correct option is A (b+2c)
Given, the expression is 
6abb2+12ac2bc(6ab)

Consider the numerator,
6abb2+12ac2bc6ab=6×a×bb2=b×b
Both the terms have b as a common factor.

12ac=2×2×3×a×c2bc=2×b×c
Both the terms have 2 and c as common factors.

By taking the common factors out, 
6abb2+12ac2bc=b(6ab)+2c(6ab)
=(b+2c)(6ab)

So, 6abb2+12ac2bc(6ab)=(b+2c)(6ab)(6ab)                                       =(b+2c)

flag
 Suggest corrections
thumbs-up
 
0 Upvotes


Similar questions
View More


People also searched for
View More



footer-image